Utilization of Social Media as a Digital Marketing Tool for the MSME "Kraft Food Ciss": Pemanfaatan Media Sosial sebagai Sarana Digital marketing pada UMKM Kraft Food Ciss - Arintha Galuh Aprilya; Muhammad Junaedi (Proceedings of The ICECRS, 2024)
General Background The rapid growth of internet adoption forces modern businesses to utilize social media for brand awareness and market survival. Specific Background Kraft Food Ciss, a culinary microenterprise, previously relied entirely on traditional commercial practices and utilized rudimentary product labels without any digital presence. Knowledge Gap Previous literature addressing digital marketing training for microenterprises lacks practical implementations of targeted online advertising and integrated link platforms. Aims This study executes a comprehensive digital marketing strategy utilizing social media management to modernize promotional activities for Kraft Food Ciss. Results The implementation of visual logo redesigns, Instagram and TikTok account management, HeyLink integration, and TikTok Ads placement drastically shifted consumer traffic, evidenced by promotional video views surging from 323 to 2200 and increased audience engagement. Novelty This intervention introduces a synchronized digital framework combining algorithmic advertising, interactive video creation, and centralized link directories specifically tailored for rural culinary operations. Implications Microenterprises must abandon exclusively traditional commerce and adopt high-quality visual content creation alongside targeted digital campaigns to secure broader market reach and ensure continuous business sustainability. Highlights Implementing targeted TikTok campaigns significantly multiplied promotional video viewership and consumer traffic. Redesigning product labels with comprehensive composition details successfully modernized traditional culinary operations. Centralizing contact information through HeyLink directly optimized consumer communication and ordering efficiency. Keywords: Digital Marketing, Social Media, Brand Awareness, TikTok Ads, Culinary Microenterprise.